Anemia and its predictors among neonates at Wachemo University teaching hospital, Central Ethiopia: a facility-based cross-sectional study - Mohamed, Kemal; Tadesse, Wondwossen; Woldesenbet, Dagmawi; Abebe, Milkias; Mussema, Abdulhakim; Tamene, Elias; Gebre, Solomon (Frontiers in Hematology, 2025)
BackgroundNeonatal anemia occurs when the blood contains lower hemoglobin levels or erythrocytes than normal. Maternal obstetric and neonatal clinical characteristics and other medical conditions can contribute to this condition.MethodsA facility-based cross-sectional study of 277 infants was conducted from October 14, 2023, to January 2, 2024. Consecutive sampling techniques were employed to enroll 277 mothers and their neonates, resulting in a response rate of 96.18%. Face-to-face interviews were conducted to gather information on neonates’ sex, sociodemographic characteristics, and nutritional status using a pre-tested structured questionnaire. A Mindray BC-3000Plus Hematology Analyzer was utilized to analyze the blood samples collected from the mothers and their neonates. All raw data were coded and entered into SPSS version 27 and analyzed using descriptive statistics, independent t-tests, and logistic regression. Statistical significance was established at a p-value of 0.05.ResultsThe overall prevalence of neonatal anemia was 21.7% (60/277). Mean hemoglobin levels were significantly lower among neonates born to anemic mothers than among those born to non-anemic mothers [(12.26 ± 2.66) Vs (13.39 ± 1.59), p <0.001). The findings from this study also showed the protective effect of taking “iron and folic acid” supplementation during pregnancy on the development of neonatal anemia (Adjusted odds ratio [AOR] = 0.15, 0.07-0.34, p <0.001).ConclusionDuring pregnancy, taking “iron and folic acid” supplements can prevent the development of neonatal anemia. Maternal anemia is correlated with lower mean hemoglobin levels in neonates. Therefore, during antenatal care follow-up, policymakers should consider implementing maternal health education regarding infant anemia and relevant health interventions to reduce the incidence of infant anemia.